2006
DOI: 10.1210/jc.2005-1803
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of the Homeostasis Model Assessment to Predict Insulin Resistance and β-Cell Dysfunction in Older People

Abstract: Context: Studies in older people have shown inconsistent agreement between homeostasis model assessment of insulin resistance (HOMA-IR) and dynamic measures of insulin action and have not evaluated HOMA ␤-cell. Objective:We compared measures of insulin sensitivity and ␤-cell function from the frequently sampled iv glucose tolerance test (FSIGT) to HOMA models.Design/Patients/Setting/Intervention: Two hundred fourteen young and old with normal glucose tolerance (NGT) and old with impaired glucose tolerance (IGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 29 publications
2
37
1
2
Order By: Relevance
“…Chang et al, 30 in a retrospective analysis, examined the HOMA model in comparison with dynamic testing of insulin sensitivity and β-cell function with the frequently sampled i.v. glucose tolerance test in a large cohort of both older men and women with normal and impaired glucose tolerance.…”
Section: Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al, 30 in a retrospective analysis, examined the HOMA model in comparison with dynamic testing of insulin sensitivity and β-cell function with the frequently sampled i.v. glucose tolerance test in a large cohort of both older men and women with normal and impaired glucose tolerance.…”
Section: Limitationmentioning
confidence: 99%
“…glucose tolerance test was moderate. The authors concluded that HOMA may detect age-related insulin resistance when comparing large populations of older people, though dynamic 30 However, the euglycaemic hyperinsulinaemic clamp is time consuming, labour intensive and requires an experienced operator to manage the technical difficulties, so it is known to be not appropriate for routine clinical applications. 31 On the other hand, the HOMA index, which reflects basal insulin sensitivity and responsiveness, has been recently used to estimate insulin resistance in critically ill patients with acute renal failure.…”
Section: Limitationmentioning
confidence: 99%
“…Some of the other studies have suggested that HOMA-IR test may have significant limitation in predicting insulin resistance and beta-cell dysfunction in older people. Chang A.M et al compared sensitivity to insulin (S(I)) and acute insulin response to glucose (AIRg) from FSIGT with HOMA models and concluded that there was a weak Agreement between HOMA beta-cell and AIR (16) . Another important factor while determining or studying HOMA-IR in patients is the different cutoff values in different population.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al [51] in a retrospective analysis, examined the HOMA model in comparison with dynamic testing of insulin sensitivity and β-cell function with the frequently sampled i.v. glucose tolerance test in a large cohort of both older men and women with normal and impaired glucose tolerance.…”
Section: Aging and Acute Insulin-resistancementioning
confidence: 99%